RHODODENDRON STANLEYI S.JAMES & ARGENT: A NEW RHODODENDRON SPECIES (ERICACEAE, SUBGENUS VIREYA) FROM PAPUA NEW GUINEA - James, S. A.; Argent, G. (Edinburgh Journal of Botany, 2017)
Rhododendron stanleyi S.James & Argent is described as a new species from Mount Yule, Central Province, Papua New Guinea. Its morphological position in the subgenus is discussed and the differences given from the most closely similar species. A note on the habitat and conservation assessment is also provided.